Evaluasi Maturitas Manajemen Keberlanjutan Bisnis pada Perusahaan Konstruksi Besar di Indonesia - Nurhadi, Didik; Wiguna, 1 Putu Artama (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2024)
The construction industry in Indonesia faces numerous disruptions, such as supply chain issues, regulatory changes, and natural disasters. Understanding the sector's preparedness for these disruptions is vital for economic and industrial resilience. This research assesses the Business Continuity Management (BCM) maturity of large Indonesian state-owned (BUMN) and private (BUMS) construction companies using an empirical model based on ISO 22301 and NFPA 1600, combined with the pairwise comparison of Analytical Hierarchy Process (AHP) for weighting factors. The maturity value is derived from the ratio of the maximum achievable score “4” to the sum product of the weighting and scores for the relevant criteria, where scores range from